Mouse (The Biblical archaeology review, 2022)
Ever since Homo sapiens domesticated grains and animals, mice have been our uninvited hangers-on, always happy to grab an easy meal and take up free lodging afforded to them by human settlement. In agricultural societies of the ancient Near East, the mouse and similar rodents were primarily thought of as vermin and a major […]